Physical Examination Findings of Painful Shoulder (Medicine Today, 2025)
Introduction with Objective: Shoulder pain and weakness are common complaints among patients, which can lead to disability and affect a person’s ability to perform daily activities. The aim of this study was to identify the physical examination findings of painful shoulder. Materials and Methods: This Prospective Observational Study was carried out among 101 patients attending at the Department of Physical Medicine and Rehabilitation, Dhaka Medical College and Hospital (DMCH), Dhaka within the defined period from July 2021 to December 2021. Ethical clearance was obtained from the Institutional Review Board (IRB) of Dhaka Medical College Hospital. Purposive sampling was done according to availability of the patients. Statistical analyses of the results were obtained by using window based computer software devised with Statistical Packages for Social Sciences (SPSS-20.1). Results: Majority of the patients (59.4%) were in 41-50 years age group where the mean age of the patients was 50.3 ± 7.9 years and 51 (50.5%) patients were male. Majority of the patients (59.4%) had shoulder pain on right shoulder. In case of active movement, the mean external rotation (in abduction) of the patients was 69.1 ± 17.5 and the mean forward flexion was 153.9 ± 17.2. On the other hand, in case of passive movement, the mean external rotation (in abduction) of the patients was 73.6 ± 15.2 and the mean forward flexion was 160.7 ± 13.7 On physical examination, 76 (75.2%) patients were Neer tests positive, 62 (61.4%) were Jobe’s test for supraspinatus positive and 37 (36.6%) were Yegarson’s test for the long head of the biceps brachii positive. Most of the patients (93.1%) were Patte’s test for infraspinatus negative. Conclusion: Appropriate physical examination of the shoulder is important for making an accurate diagnosis and distinguishing certain pathologies of the shoulder.Medicine Today 2025, Vol.37 (2): 230-232